The effects of individual and combination of asiatic acid and madecassoside derived from Centella asiatica (Linn.) on the viability percentage and morphological changes of mouse macrophage cell lines (J774A.1) - Nurul Hikmah, Harun; Wan Amir Nizam, Wan Ahmad; Rapeah, Suppıan (2018)
Asiatic acid and madecassoside are the two pentacyclic triterpenoid compounds derived from Centella asiatica (Linn.), which believed to possess major contribution in many related pharmacological activities. This research is conducted to determine the viability and the morphological changes of macrophage cells after treating with individual and combination of the mentioned compounds by using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay and observing through image analyzer system, respectively. Results displayed that only AA at high doses 25 and 50 μg/ml, exhibited mild inhibition of mouse macrophage cells J774A.1 viability with only the latter dose able to alter the morphology of the cells after 24 hours of treatment. Therefore, both compounds either in sole or mix form were harmless to the cells (IC50 > 50 μg/ml). Interestingly, the combination treatment also enhanced the macrophage cell viability higher than their sole treatment in every concentration. As a consequence, the bioactive compounds at none-cytotoxic level can be applied in any in-vitro further studies such as immunomodulatory and antiinflammatory in order to prove the local traditional claim on the herb and for future benefit in a new prospective of natural product-based drugs development.